2007
DOI: 10.2223/jped.1601
|View full text |Cite
|
Sign up to set email alerts
|

Remission status follow-up in children with juvenile idiopathic arthritis

Abstract: ResumoObjetivo: Caracterizar a atividade inflamatória articular e sistêmica na artrite idiopática juvenil (AIJ), determinando o estado de remissão com e sem uso de medicação.Métodos: Um total de 165 casos de AIJ, acompanhados em média por 3,6 anos, foram revisados para caracterização de episódios de inatividade, remissão clínica com e sem medicação. Os dados obtidos foram analisados por meio de estatística descritiva, análise de sobrevida, comparação das curvas de Kaplan-Meier, teste de log rank e análise de r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
3
0
5
Order By: Relevance
“…Fernandes et al [28] reviewed 108 patients with JIA who had a minimum follow-up of 1 year (median follow-up, 4.6 years) from 1986 to 2005. A total of 53% (57 of 108) of patients had a total of 71 episodes of ID, of which 51% (36 of 71) achieved CR.…”
Section: Recent Studies Using Preliminary Remission Criteriamentioning
confidence: 99%
“…Fernandes et al [28] reviewed 108 patients with JIA who had a minimum follow-up of 1 year (median follow-up, 4.6 years) from 1986 to 2005. A total of 53% (57 of 108) of patients had a total of 71 episodes of ID, of which 51% (36 of 71) achieved CR.…”
Section: Recent Studies Using Preliminary Remission Criteriamentioning
confidence: 99%
“…Afeta crianças de ambos os sexos antes dos 16 anos, e a remissão completa só é vista em 75% dos pacientes [1][2][3] . O cuidado de uma criança com AIJ geralmente repousa sobre familiares, que acabam sendo submetidos a dois tipos diferentes de sobrecarga emocional: o estresse objetivo e o subjetivo 4 .…”
Section: Introductionunclassified
“…A uniform definition of remission in certain subtypes of JIA for use in clinical trials has been developed and preliminarily validated (8, 9). Retrospective cohort studies of JIA using these criteria have shown that remission is achieved in 26–40% of patients (10–14). These studies also showed that remission rates differed among JIA subtypes.…”
Section: Introductionmentioning
confidence: 99%